Le luxe des montres (xixe-xxe siècle) : réputation et identité de l’horlogerie de Genève - Nadège Sougy (Études Caribéennes)
At the end of the 19th century, the watchmakers of Geneva are confronted to the arrival of products retaking abusively its brands and the name of Geneva. In response, watchmakers, retailers and public actors decided to protect this economic sector. One of the solutions picked up was to identify Geneva-made watches by certifying their quality. In 1886, the creation of a hallmark of the State and the Republic of Geneva is the first label associating the expertise of a territory with the technical quality of its products. Originally defensive, the hallmark promotes high-quality products characterized by a good invoice, a reliability and their origin, a branding of the luxury of Geneva watches.